Impaired Vision Function Due to Use of Gadget - Syafi'in Syafi'in; Byba Melda Suhita (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Background: The disruption of the visual function resulting from the use of gadgets, by explaining the disturbance of the visual function that occurs and the proper and correct use of gadgets, which can maintain vision function, especially for children and adolescents Method: SLiterature sources were searched using data bases: Google Scholar, Pubmed, Proquest, Science Direct, and Sinta using keywords: computer, gadget, portable display, smartphone and eye, myopia, vision, visual. With boolen operators (AND, OR, NOT). The articles obtained were published between January 2015 and October 2020 for selection according to the objectives of the literature review and obtained as many as fifteen studies included in this literature review. Result: Prolonged use of gadgets and the like was significantly associated with decreased visual acuity and the onset of myopia (8 studies), as well the occurrence of one or more Computer Vison Syndrome in the eye organs (7 studies). Conclusion: The use of gadgets is not the only main cause of health problems, but contributes significantly to various health problems, especially impaired vision, namely decreased visual acuity, myopia, and computer vision syndrome. Proper management of gadget usage can prove beneficial in understanding education and other fields better whereas excessive use can lead to various health problems.